Parents’ interest in their child’s education and children’s outcomes in adolescence and adulthood: Does gender matter? - Povey, Jenny; Mitrou, Francis; Haynes, Michele; Campbell, Alice K; Hancock, Kirsten J (My University, 2017)
There has been a dearth of research utilising interactional models of parent and child gender to investigate whether there are gender-specific effects in relationships between parent engagement and children’s cognitive and non-cognitive outcomes. This study drew upon data from the Longitudinal Study of Australian Children, and used adolescents’ reports of the interest shown by their parents in their education as well as parents’ retrospective reports of the interest shown by their own parents when they were growing up. We found no evidence of gender-specific effects for the outcomes of academic achievement, educational expectations or educational attainment in adulthood. Mothers’ and fathers’ interest was associated with the self-concept of their children, and these associations were stronger in opposite-gender children.
International Journal of Educational Research
Keywords: Families and relationships; Gender; Families and relationships; Gender